Design of a nonlinear controller using feedback linearisation based on backstepping technique for magnetic levitation system. (2016) - Tandon, Bhawna; Narayan, Shiv; Kumar, Jagdish
This study proposes a feedback linearisation based on the back-stepping method to design a nonlinear controller with a goal of improving both steady state and transient stability of a magnetic levitation system. The feedback linearisation based on back-stepping technique is the combination of the two techniques mentioned i.e. feedback linearisation and backstepping. It uses backstepping design process, designs a sequence of 'virtual' systems of relative degree one, reduces the relative degree by one by choosing a 'virtual' input, achieves passivity with respect to a 'virtual output', and the last 'virtual output' is used to close feedback loop. Unlike the direct feedback linearisation method, the proposed method does not require a linear controller. Moreover, there is no need to know the exact nonlinear model of the system. Back stepping process of the controller guarantees its robustness against disturbances and uncertainties.